Avaliação de novo teste imunocromatográfico rápido para o diagnóstico da leishmaniose visceral humana - Almeida, Meirielly Lima (2015)
Introduction: Human Visceral Leishmaniasis (HVL) is a major public health problem in Brazil with more than 3,500 new cases per year and can lead to death if not treated. The gold standard for diagnosis is the parasitological test, but it is an invasive, expensive technique, and does not present ideal sensitivity. The serologic Indirect Immunofluorescence test is available in the public health system, however, this low sensitive that technique that requires time, equipment. Currently, there has been an investment in the development of rapid immunochromatographic tests that show good sensitivity and specificity, in addition to being faster, practical and economical. The rK39 is the immunoassay currently used for the diagnosis of HVL and has international production. Methodology: This study evaluated three new rapid immunochromatic tests (TRs) for screening of HVL, these tests were produced by Gonçalo Moniz Research Center (Fiocruz). The three tests were identified as: Test 1, comprising the recombinant antigen Lci1A; Test 2, formed by the recombinant antigen Lci2B; and Test 3, comprising the conjugate of the two antigens. A total of 159 sera from different individuals were used. The group "cases" consisted of 79 sera from patients diagnosed with VL, it considered compatible clinical symptoms (fever associated with splenomegaly and hepatomegaly), bone marrow culture and / or rK39 positive test, pancytopenia and therapeutic success. The group of "non-cases" consisted of 90 sera from patients with other diseases and healthy people. Results: The sensitivity values were good for the three tests (over 90%), but the specificity of test 1 was very low (10,0%). As for tests 2 and 3, the specificities were 90.0% and 83.3%, respectively. Conclusion: The results indicate that both test 2 has potential for use as diagnostic screening for VL in humans.